Broncholaveolar lavage to detect cytomegalovirus infection, latency, and reactivation in immune competent hosts. Issue 8 (2nd February 2016) - Mansfield, Sara; Dwivedi, Varun; Byrd, Sara; Trgovcich, Joanne; Griessl, Marion; Gutknecht, Michael; Cook, Charles H.
Abstract : Roughly 1/3rd of immune competent patients will reactivate latent cytomegalovirus (CMV) during critical illness. There are no standard methods to detect reactivation, and some investigators have postulated that presence of DNA in BAL fluid is indicative of viral replication. To test this hypothesis, we used a murine model that allows inclusion of matched healthy controls which is not possible in human studies. BALB/c mice infected with Smith‐murine CMV or PBS (mock) had BAL evaluated 7, 14, or 21 days after acute infections, during latency, or during bacterial sepsis. Plaque assay, PCR, and rtPCR were performed on BALs and concomitantly obtained lung tissue. BAL cellular compositions, including tetramer evaluation of CMV‐specific T cells were evaluated by flow cytometry. CMV DNA were detected in BAL at all time‐points during acute infection, becoming undetectable in all mice during latency, then were detected again during bacterial sepsis, peaking 3 weeks after onset. mCMV specific T‐cells were most numerous in BAL after acute viral infections, decreasing to low levels during latency, then fluctuating during bacterial sepsis. Specifically, mCMV‐specific T‐cells contracted at sepsis onset, expanding 2–4 weeks post‐sepsis, presumably in response to increased viral loads at that time point. Altogether, our results support the use of BAL PCR for the diagnosis of CMV replication in immune competent hosts. Additionally, we demonstrate dynamic changes in CMV‐specific T cells that occur in BAL during CMV infection and during sepsis induced viral reactivation. J. Med. Virol. 88:1408–1416, 2016 . © 2016 Wiley Periodicals, Inc.